2013
DOI: 10.1182/blood.v122.21.4886.4886
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/Akt Signaling Interacts With Wnt/β-Catenin Signaling But Does Not Induce An Accumulation Of β-Catenin In The Nucleus Of Acute Lymphoblastic Leukemia Cell Lines

Abstract: Signaling pathways play essential roles in biological processes as development, cell proliferation and homeostasis. The accurate modulation of signaling pathways, their adapted interaction and their time- and tissue-specific adjusted regulation are required for normal cell development. PI3K/Akt and Wnt/β-Catenin signaling pathways act as key regulators in cell proliferation, differentiation and growth. Both signaling pathways include GSK3β as a common protein, which may mediate an interaction and cross-talk be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…AKT1 is an important gene in the PI3K/AKT pathway. Studies have been conducted about the cross-talk between Wnt/β-catenin and PI3K/AKT signaling pathways [ 63 , 64 ]. Han et al have reported that inhibition of PI3K/AKT suppressed transcription through β-catenin in glioblastoma cells [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…AKT1 is an important gene in the PI3K/AKT pathway. Studies have been conducted about the cross-talk between Wnt/β-catenin and PI3K/AKT signaling pathways [ 63 , 64 ]. Han et al have reported that inhibition of PI3K/AKT suppressed transcription through β-catenin in glioblastoma cells [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, the Wnt/β-catenin signaling pathway promotes cell survival and cell growth (Ali-Harthi, 2012; Langhammer et al, 2013; Polakis et al, 2012), in part by stimulating Akt signaling pathways (Fukumoto et al, 2001; Kaler et al, 2009; Kim et al, 2007; Langhammer et al, 2013). It is also well established that an active Akt pathway promotes cell survival (Manning and Toker, 2017; Martelli et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Mice latently infected with wild-type HSV-1 contain significantly more TG neurons that express ␤-catenin than those in an LAT-null mutant (33). Akt family members and the Wnt signaling pathway form a positive regulatory loop (34)(35)(36)(37)(38)(39), suggesting that these signaling pathways promote the maintenance of latency.…”
mentioning
confidence: 99%